Analysis of the residential demand of basic services in Spain using a censored QUAIDS model - Gálvez, Pablo; Mariel, Petr; Hoyos, David (Estudios de Economía, 2016)
This paper analyses the Spanish residential demand of a bundle of goods conforming the basic services of the households (i.e. electricity, natural gas and drinking water) in 2012. The analysis is made using a QUAIDS model modified in order to consider the censoring in the consumption of natural gas following the approach of Tauchmann (2010), one of the latest advances in this field. The results show that the demand for electricity and drinking water is less sensitive to the variations in prices and household’s income than that of natural gas.